The Politics of Islamic Education in The Caliphate of Umar Ibn Khattab - Muhamad Tisna Nugraha (IAIN Salatiga, 2020)
This study aims to reveal the political system of education in the reign of the second caliph, Umar ibn Khattab. The method used in this study is a qualitative research method with a literature study. The process of data collection was conducted through documentation and observation techniques so that the available literature sources then studied, compared, and presented in words by the researcher. The results of the study are that political policies in the early period of Islam helped determine the development and progress of education in the area of the central government to the conquered regions, such as al-Quds (Palestine), Sham, Sassanid (Persia), Egypt and others. The system can be seen from the regulations regarding the appointment of the educators (teachers and lecturers), the emergence of a bilingual learning method, the periodic payment of teacher salaries, and the tiered education system, starting from the basic to the madrasah level. Furthermore, it was noticeable that since the reign of Umar ibn Khattab, access to Islamic education has been widely accessible by society despite the race, social and economic status.